Isolation of the wild-type rubella virus in rabbit kidney cell line RC-IAL - Cristina A. Figueiredo; Maria I. Oliveira; Ana M. S. Afonso; Márcia Theobaldo; Aurea S. Cruz; Suely P. Curti (Sociedade Brasileira de Patologia Clínica, 2004)
The present study describes the isolation and growth the wild-type rubella virus in RC-IAL. The susceptibility of a rabbit kidney (RC-IAL) to the RV RA 27/3 strain was previously reported by us(4). Samples of 20 patients with suspected cases of rubella infection were tested by serology, virus isolation and nested PCR. The sera were tested by Elisa for the detection of rubella virus antibodies and nested PCR assay was performed to detect RNA virus. The samples of urine, blood, fragments of placenta and amniotic fluid were inoculated in the RC-IAL (rabbit kidney, Institute Adolfo Lutz) and Sirc (rabbit cornea) cell lines. Rubella virus was isolated in samples from 14 of the patients. The CPE (cytopathic effect) was visualized by phase contrast and RV RNA was amplified by nested PCR.The results obtained showed that the cellular lineage RC-IAL is an excellent substratum for isolation of the rubella virus. These findings are important since this is one the few cell lines described in literature that presents a cytopathic effect, so that it can be used to isolate the virus of the clinical specimens.